How Does Exposure to COVID-19 Influence Health and Income Inequality Aversion? - Miqdad Asaria; Joan Costa-Font; Frank A. Cowell (Institute of Labor Economics (IZA), 2021)
We study whether exposure to COVID-19 has affected individual aversion to health and income inequality in the UK, Italy, and Germany, as well as the effect of personal shocks on employment (redundancies, government replacement salary and unemployment), income and health directly linked to COVID-19. We find that conditioned on risk aversion and relevant covariates (income, education, demographics), individuals who have experienced either a health or an financial shock during the COVID-19 pandemic, exhibit lower inequality aversion in terms of health and income, compared to those who have not experienced these shocks. Comparing levels of health and income inequality aversion in the UK between the years 2016 and 2020 we find a significant increase in inequality aversion from 2016 to 2020 in both health (17.3%) and income domains (8.8%). However, our difference-in-differences (DiD) for treatment (risk) groups defined in terms of age, region and personal exposure to health and income shocks in 2020 compared to 2016, does not indicate any additional difference in inequality aversion. The exception being individuals who are both in a high-risk age group and at the same time also experienced a health shock in 2020 compared to 2016, which are significantly more inequality averse in both health and income domains.
Keywords: I18; I30; I38; 330; inequality aversion; income; health; COVID-19; attitudes to inequality; employment shocks; health shocks; difference in differences